Bacteria and fungi as major bio-sources to fabricate silver nanoparticles with antibacterial activities. Issue 6 (3rd June 2022) - Alavi, Mehran
ABSTRACT: Introduction: Mitigation of infectious diseases resulted from antibiotic-resistant bacteria is difficult by current antibiotics. Metal and metal oxide nanoparticles specifically Ag nanoparticles can be efficient antibacterial agents considering their biocompatibility. In this way, biosynthesis of Ag nanoparticles by living organisms or their metabolites has obtained more attention compared to chemical or physical methods. Areas covered: Bacteria and fungi in extracellular and intracellular pathways and related primary and secondary metabolites can synthesize Ag nanoparticles with synergistic antibacterial activity against bacterial pathogens. Expert opinion: Bacteriostatic and bactericidal effects of these nanoparticles can lead by production of reactive oxygen species and inactivation of biological macromolecules such as proteins and nucleic acids. The present review has tried to discuss recent progress and challenges about biosynthesis mechanisms and antibacterial activity of Ag nanoparticles bio-inspired by archaebacteria, actinomycetes, cyanobacteria, and fungi.